Inflorescence, spikelet, and floral development in Panicum maximum and Urochloa plantaginea (Poaceae) - Reinheimer, Renata (2005)
Inflorescence development in Panicum maximum and Urochloa plantaginea was comparatively studied with scanning electron and light microscopy to test the transfer of P. maximum to Urochloa and to look for developmental features applicable to future cladistic studies of the phosphoenol pyruvate carboxykinase (PCK) subtype of C4 photosynthesis clade (P. maximum and some species of Brachiaria, Chaetium, Eriochloa, Melinis, and Urochloa). Eleven developmental features not discernable in the mature inflorescence were found: direction of branch differentiation; origins of primary branches; apical vs. intercalary development of the main axis; direction of spikelet differentiation; direction of glume, lemma and palea differentiation; position of the lower glume (in some cases); size of the floret meristem; pattern of distal floret development; pattern of gynoecium abortion; differential pollen development between proximal and distal floret; and glume elongation. Inflorescence homologies between P. maximum and U. plantaginea are also clarified. Panicum maximum and U. plantaginea differ not only in their mature inflorescence structure but also in eight fundamental developmental features that exclude P. maximum from Urochloa. The following developmental events are related to sex expression: size of floret meristem, gynoecium abortion, pollen development delay in the proximal floret, glume elongation and basipetal floret maturation at anthesis.